If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -65 = 2x Reorder the terms: -65 + 7x = 2x Solving -65 + 7x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -65 + 7x + -2x = 2x + -2x Combine like terms: 7x + -2x = 5x -65 + 5x = 2x + -2x Combine like terms: 2x + -2x = 0 -65 + 5x = 0 Add '65' to each side of the equation. -65 + 65 + 5x = 0 + 65 Combine like terms: -65 + 65 = 0 0 + 5x = 0 + 65 5x = 0 + 65 Combine like terms: 0 + 65 = 65 5x = 65 Divide each side by '5'. x = 13 Simplifying x = 13
| x+18=-12 | | 2x-31=18 | | 10m+120=4m+150 | | 2x+3(5-x-12)=4(x+2) | | 228=w*2w+6 | | 2x-5=x+26 | | 199=x^2+2x | | 3z-4=2iz+5i | | 6.05+4.7c=3.4c-6.95 | | 3(7p-1)=7p-3 | | 16=x-y | | -6w^2+23w+4=0 | | 5x-4(-5y+5x)-3y= | | -4t+10=-6t-20 | | -25=5(4q-10)-5q | | Y=0.5x+6 | | -2x+4(1-3x)=2x-4(6x+5) | | 1-4n+3=4n-7n-2 | | 9(5b+4)= | | -(a+1)=7-a | | y+30=8 | | 0.3(x+100)+1.5=111 | | 36x-90-30x-60-3x-15=16x+24-6x+6-6+8x | | 10.19-3.3q+7.2q=2.8q-11.59 | | 3x+30=X-2 | | 3x+7x=4x-9 | | 4ab+4a= | | -6.5z+2.26=-17.74-7.5z | | -5w-(7z-6w)-2z= | | 12-m-9m=-20-12m | | x+8=1-6x | | -4w-5(-7x+4w)+6x= |